Clinical Comparison of QUANTA Flash dsDNA Chemiluminescent Immunoassay with Four Current Assays for the Detection of Anti-dsDNA Autoantibodies - Maria Infantino; Francesca Meacci; Chelsea Bentow; Peter Martis; Maurizio Benucci; Antonella Afeltra; Amelia Rigon; Fabiola Atzeni; Piercarlo Sarzi-Puttini; Mariangela Manfredi; Michael Mahler (Journal of Immunology Research)
Introduction. The objective of the present study was to compare QUANTA Flash dsDNA, a chemiluminescent immunoassay (CIA) on the BIO-FLASH, a rapid-response chemiluminescent analyzer, to three other anti-dsDNA antibody assays and to Crithidia luciliae indirect immunofluorescence test (CLIFT). Methods. In the first part of the study, 161 samples, 61 from patients suffering from systemic lupus erythematosus (SLE) and 100 from a disease control group, were tested by QUANTA Flash dsDNA CIA, QUANTA Lite dsDNA SC ELISA, BioPlex 2200 multiplex flow immunoassay (MFI), ImmuLisa dsDNA ELISA, and NOVA Lite CLIFT. A second cohort of 69 SLE patients was then tested by QUANTA Flash dsDNA and CLIFT to expand the study. Results. The overall qualitative agreements varied between 77.0% (NOVA Lite CLIFT versus QUANTA Lite) and 89.4% (ImmuLisa versus NOVA Lite CLIFT). The clinical sensitivities for the anti-dsDNA antibody tests varied from 8.2% (NOVA Lite CLIFT) to 54.1% (QUANTA Lite), while the clinical specificities varied from 88.0% (BioPlex 2200) to 100.0% (NOVA Lite CLIFT). Good correlation was found between QUANTA Flash dsDNA and NOVA Lite CLIFT. Conclusion. Significant variations among dsDNA methods were observed. QUANTA Flash dsDNA provides a good combination of sensitivity and specificity for the diagnosis of SLE and good agreement to CLIFT.